2022
DOI: 10.1021/acs.jafc.2c04108
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Alters Muscle Fiber-Type Composition and Promotes Mitochondrial Biogenesis through the AMPK Signaling Pathway in Healthy Pigs

Abstract: Ellagic acid (EA), because of its remarkable health-promoting ability, has aroused widespread interest in the fields of nutrition and medicine. However, no reports showed that EA regulates mitochondrial biogenesis as well as muscle fiber-type composition in pigs. Our study found that dietary 75 and 150 mg/kg EA obviously augmented the slow myosin heavy chain (MyHC) protein level, the number of slow-twitch muscle fibers, and the activity of malate dehydrogenase (MDH) in the longissimus thoracis (LT) muscle of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…To ensure proper mitochondrial function, the process of mitochondrial biogenesis plays a crucial role and is by various transcription factors such as NRF-1, PGC-1α, and TFAM that enhance not only the quantity but also the quality of mitochondria. NRF1 is a crucial transcription factor in regulating mitochondrial function and gene expression, while TFAM is an essential DNA-binding protein that controls DNA replication and transcription, as well as participates in mitochondrial fusion and fission [32] . The study found that USM had a significant impact on gene expression, leading to an increase in mitochondrial biogenesis and maintenance of normal cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure proper mitochondrial function, the process of mitochondrial biogenesis plays a crucial role and is by various transcription factors such as NRF-1, PGC-1α, and TFAM that enhance not only the quantity but also the quality of mitochondria. NRF1 is a crucial transcription factor in regulating mitochondrial function and gene expression, while TFAM is an essential DNA-binding protein that controls DNA replication and transcription, as well as participates in mitochondrial fusion and fission [32] . The study found that USM had a significant impact on gene expression, leading to an increase in mitochondrial biogenesis and maintenance of normal cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the role of EA was widely showed in skeletal muscles. Ingrowing-finishing pigs, EA was involved in regulation of muscle fiber-type composition as represented by augmenting MyHC level and MDH activity 12 . In diabetes-induced muscle atrophy, EA decreased genes expressions related to protein degradation in gastrocnemius 13 .…”
Section: Discussionmentioning
confidence: 99%
“…As an energy provider, mitochondria are more abundant in oxidized muscle fibers [ 15 ]. Mitochondrial function and number are positively regulated by PGC-1α signaling, and consequently promote oxidative myofibers development [ 16 , 17 ]. Accordingly, enhancing the proportion of oxidative myofibers in skeletal muscle can contribute to improving meat quality and human’s living standards.…”
Section: Introductionmentioning
confidence: 99%